Binding 13 - Walsh, Chloe (Fiction writer) (Walsh, Chloe (Fiction writer). Boys of Tommen, 2023)
Johnny Kavanagh has everything going for him. On the rugby pitch, he's a force to be reckoned with. Primed for stardom, he's heading straight for the top. Nothing can possibly get in his way, right? Not even the shy new girl at Tommen College. The one with the sad eyes and hidden bruises. The one that distracts him like no one ever has. Plagued with a hidden injury and desperate to impress the scouts watching his every move, Johnny has been placed on a pedestal so high, he has no room to make mistakes. Striving to maintain balance, and on the crest of the International Summer Campaign, Johnny needs to keep his head in the game. He needs to stay focused, and cannot afford to let distractions get in the way of the bigger picture. But what happens when a lonely girl with sad eyes becomes the only picture? Life has never been easy for Shannon Lynch. Bullied and tortured, she arrives at Tommen College mid-way through the school year praying for a fresh start and desperate to shake off the demons that plague her. On her very first day at the prestigious private school, she comes into contact with the notorious Johnny Kavanagh. Thrown through a hoop over her feelings for him, and desperate to keep a low-profile, Shannon finds herself once again the target of bullies as she forms a fragile alliance with rugby's rising star. Falling into a complicated friendship and grappling with their undeniable chemistry, Johnny and Shannon must face obstacles that threaten their relationship. Two teenagers from opposite sides of the tracks collide. Friendship, first love, rising fame, horrifying secrets, and pain all fuel together in Binding 13, the explosive first installment of a brand-new series from Chloe Walsh. Based in Ireland, the Boys of Tommen series is bound to captivate and lure you into the world of rugby, love, and teenage heartbreak.